Primary Nephrotic Syndrome in Adults as a Risk Factor for Pulmonary Embolism: An Up-to-Date Review of the Literature - Aibek E. Mirrakhimov; Alaa M. Ali; Aram Barbaryan; Suartcha Prueksaritanond; Nasir Hussain (International Journal of Nephrology)
Patients with nephrotic syndrome are at an increased risk for thrombotic events; deep venous thrombosis, renal vein thrombosis, and pulmonary embolism are quite common in patients with nephrotic syndrome. It is important to note that nephrotic syndrome secondary to membranous nephropathy may impose a greater thrombotic risk for unclear reasons. Increased platelet activation, enhanced red blood cell aggregation, and an imbalance between procoagulant and anticoagulant factors are thought to underlie the excessive thrombotic risk in patients with nephrotic syndrome. The current scientific literature suggests that patients with low serum albumin levels and membranous nephropathy may benefit from primary prophylactic anticoagulation. A thorough approach which includes accounting for all additional thrombotic risk factors is, therefore, essential. Patient counseling regarding the pros and cons of anticoagulation is of paramount importance. Future prospective randomized studies should address the question regarding the utility of primary thromboprophylaxis in patients with nephrotic syndrome.